보육시설에서의 영아-교사 상호작용과 영아의 발달수준, 교사의 민감성 및 초기 가정환경 간의 관련성에 관한 연구 - 최은정(Eun Jung Choi); 하지영(Ji Young Ha); 서소정(So Jung Seo) (Korean Journal of child studies, 2009)
This study investigated relationships among infant development, teacher's sensitivity, home literacy environment, and infant-teacher interaction in the child care setting. Verbal and behavioral interactions between 30 2-year-old infant-teacher pairs were video-recorded during free play activities; teachers' sensitivity was observed by trained observers; infant development was assessed by teachers; data on the early home literacy environment were gathered through maternal self-reported questionnaires. Data were analyzed by descriptive statistics, t-tests, and correlation analyses. Results indicated that boys showed more naming; girls showed more physical contact with teachers. Infants high in overall developmental level showed more behavioral interaction with teachers. Teacher's sensitivity correlated positively with behavioral imitating and negatively with questioning and nodding. Verbal interaction in the home correlated positively with nodding.